If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -10 = 6x + -1(x + 2) + (3 + -1x) Reorder the terms: -10 + 15x = 6x + -1(x + 2) + (3 + -1x) Reorder the terms: -10 + 15x = 6x + -1(2 + x) + (3 + -1x) -10 + 15x = 6x + (2 * -1 + x * -1) + (3 + -1x) -10 + 15x = 6x + (-2 + -1x) + (3 + -1x) Remove parenthesis around (3 + -1x) -10 + 15x = 6x + -2 + -1x + 3 + -1x Reorder the terms: -10 + 15x = -2 + 3 + 6x + -1x + -1x Combine like terms: -2 + 3 = 1 -10 + 15x = 1 + 6x + -1x + -1x Combine like terms: 6x + -1x = 5x -10 + 15x = 1 + 5x + -1x Combine like terms: 5x + -1x = 4x -10 + 15x = 1 + 4x Solving -10 + 15x = 1 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -10 + 15x + -4x = 1 + 4x + -4x Combine like terms: 15x + -4x = 11x -10 + 11x = 1 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 + 11x = 1 + 0 -10 + 11x = 1 Add '10' to each side of the equation. -10 + 10 + 11x = 1 + 10 Combine like terms: -10 + 10 = 0 0 + 11x = 1 + 10 11x = 1 + 10 Combine like terms: 1 + 10 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| -16x^2+78x+6=0 | | bx-6=cx+4 | | -8=3/7x | | h+2(h-6)=18 | | 10x+4y+5z=170 | | 4(x+3)=6(2x-5) | | -7/4c=-7 | | F(7)-f(4)/7-4 | | -18=2/3x | | 3(x+7)=6(-3+7x) | | -5/6d=5 | | (1.6x^3+4.9x^2-3.7x)-(-4.1x^3-4.8x^2+95)= | | Q=t/12 | | 0.5a-3=7-3/4a | | 5(2x-2)=5(x-1) | | 7u+5+18u+18=248 | | -7(2x-5)+5(3x-5)-2=6-9 | | 21+1.5h=10+2.75h | | (-1/6x^6)(-1/5x) | | -7(2x-5)+(3x-5)=6-9 | | 90=18y+30-5y-5 | | -2(3y-3)-y=-3(y-2) | | 5+c=8 | | 3=-3(11-s)/7 | | .3(8)+x=.5(8+x) | | 6y-14(-2y+8)=432 | | D=4m+9 | | 2.5+5.75=2+3.75a | | 4y=16-8x | | 3(2x-4)=32-5(x-2) | | 156=18x+21+8x+5 | | 2(3x+4)=-5(5x-3) |